Soil investigation properties of soils by using different methods - Muhammad Mustaqim Ponimin, 1995-, author 614105; Nor Zuraraihetty Mohd. Yunus, supervisor 610460; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam) - Universiti Teknologi Malaysia, 2018